ANALYSIS OF SCIENCE PROCESS SKILLS THROUGH PRACTICUM ON PLANT GROWTH AND DEVELOPMENT AT THE FIRST SEMESTER STUDENTS OF PRIMARY TEACHER EDUCATION STUDY PROGRAM - Anna Roosyanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The nature of Science is as products, processes, and attitudes. In the process of finding facts, concepts, principles, theories, and laws carried out through the science process skills, and in their application involves a scientific attitude. This study aims to analyze the science process skills of first semester students of primary teacher education study program through the Science practicum on the subject of Plant Growth and Development. This research was a descriptive research with an ex post facto quantitative approach. This research was conducted on all of the first semester students in the primary teacher education study program at Wijaya Kusuma University Surabaya in the academic year 2019-2020. The instruments used in this research were the science process skills observation sheet and the plant growth and development practicum worksheet based on the science process skills. The results showed that the most difficult aspect of basic science process skills were predicting skill, and the easiest was observating skill. The most difficult aspect for integrated science process skills were defining variables operationally. The easiest was conducting investigations or experiment, and organizing data into tables and graphs.